2000
DOI: 10.1097/00007632-200003010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic Lordosis and Pelvic Balance on Repeated Standing Lateral Radiographs of Adult Volunteers and Untreated Patients With Constant Low Back Pain

Abstract: The pelvic radius technique is recommended for evaluating lordosis to the pelvis because this approach provided not only good measurement reliability on standing radiographs for lumbopelvic lordosis, but also determination of pelvic balance over the hips and the option to assess pelvic morphology quantitatively. Lumbopelvic lordosis and pelvic balance were strongly correlative. This finding, along with higher reliability and lower longitudinal variation on repeated radiographs, indicated greater clinical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(140 citation statements)
references
References 20 publications
7
129
2
2
Order By: Relevance
“…Maybe, interindividually varying soft tissue thicknessespecially fat and muscles in the lumbar back regionpartially covered specific bony spinal alignment patterns in the indirect spine shape reconstruction based on surface topography, although rasterstereography was validated in terms of X-ray comparisons [3][4][5]. This could possibly explain why we did not find systematic effects for a flatter lordosis in younger patients comparable to radiological studies [1,13].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Maybe, interindividually varying soft tissue thicknessespecially fat and muscles in the lumbar back regionpartially covered specific bony spinal alignment patterns in the indirect spine shape reconstruction based on surface topography, although rasterstereography was validated in terms of X-ray comparisons [3][4][5]. This could possibly explain why we did not find systematic effects for a flatter lordosis in younger patients comparable to radiological studies [1,13].…”
Section: Discussionmentioning
confidence: 76%
“…When the most predictive factor for the development of low back pain-earlier back pain periods-could be controlled statistically, a flatter lumbar lordosis angle could be identified as a risk factor [1]; mathematical modeling studies reported a tendency for a flatter lordosis angle in chronic low back pain patients, too [11]. Some radiological findings in adults confirmed a flatter lumbar lordosis to be associated with chronic low back pain [13]. However, controversy exists on this potential association [10,15], and-despite clinical relevance-specific X-ray patterns between acute and chronic low back pain patients could not be identified for the lumbosacral transition [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical normal values for spinopelvic parameters can also be estimated from mathematical relations (Table 2). Otherwise, to analyze segmental changes, we have to keep in mind that the L4-S1 segment provides the 2/3 of the total lumbar lordosis [9,11,20].…”
Section: Compensatory Mechanismsmentioning
confidence: 99%
“…Similarly, patients with chronic low back pain and lumbar degenerative disease present with modifications of sagittal balance and are characterized by anterior sagittal imbalance, loss of lumbar lordosis, and increase of pelvis tilt [1,2,8,9]. The anterior imbalance in patients' population is mainly due to the loss of lumbar lordosis even if the part of the structural loss of lordosis and postural part may be difficult to differentiate.…”
Section: Introductionmentioning
confidence: 99%